Histórias de resistências de mulheres escravizadas em Pernambuco (1830-1856) - Simas, Tatiany de Oliveira Simas (2017)
Crimes and transgressions practiced by enslaved women in opposition to the slave system as an instrument of contestation were present in the Brazilian scenario prevailing in the relations between masters and captives. In this way, this work, based on the social history of slavery, investigated various forms of resistance, such as escapes, daily infractions and homicides practiced by enslaved women, identifying these actions as an act of opposing slavery. In our study, enslaved women are highlighted as agents and historical protagonists and, for this, we have investigate their struggles, the mechanisms and strategies of resistance built by them that sought better living conditions and spaces of autonomy in captivity in their varied social relations. We analyzed the experiences of women who lived in urban and rural areas. So we use as historical sources, the periodicals available at the Digital Library of the National Library, in documents dealing with criminal occurrences of the Comarcas of the province of Pernambuco, and are available in the State Public Archive of Pernambuco, and requests for commutation that were found in the Fund of the Ministry of Justice, located in the National Archive of Rio de Janeiro. All these documents revealed the transgressions that were committed, the reasons and the circumstances in which they occurred and which penalties were applied to the women who were against the oppressive system of slavery. The period analyzed are the 30s and 50s of 19th century in the province of Pernambuco. Finally, we emphasize that this study is linked to the Regionalities and History Research Line of the Postgraduate Program in History at the Federal University of Paraíba (UFPB).